2017
DOI: 10.1016/j.ymthe.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

A Proof-of-Concept for Epigenetic Therapy of Tissue Fibrosis: Inhibition of Liver Fibrosis Progression by 3-Deazaneplanocin A

Abstract: The progression of fibrosis in chronic liver disease is dependent upon hepatic stellate cells (HSCs) transdifferentiating to a myofibroblast-like phenotype. This pivotal process is controlled by enzymes that regulate histone methylation and chromatin structure, which may be targets for developing anti-fibrotics. There is limited pre-clinical experimental support for the potential to therapeutically manipulate epigenetic regulators in fibrosis. In order to learn if epigenetic treatment can halt the progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 56 publications
3
64
0
Order By: Relevance
“…EZH2 represses peroxisome proliferator‐activated receptor gamma, which is a negative master regulator of HSC activation . Furthermore, targeted delivery of the histone methyltransferase inhibitor 3‐deazaneplanocin A, selectively to HSCs, using an antibody‐liposome targeting vehicle, attenuated carbon tetrachloride‐induced liver fibrosis in mice . In contrast, the current results demonstrate that pharmacologic inhibition of EZH2 degradation is actually protective during biliary fibrosis whereas selective deletion of EZH2 in cholangiocytes exacerbates biliary fibrosis, consistent with our previous finding .…”
Section: Discussionsupporting
confidence: 91%
“…EZH2 represses peroxisome proliferator‐activated receptor gamma, which is a negative master regulator of HSC activation . Furthermore, targeted delivery of the histone methyltransferase inhibitor 3‐deazaneplanocin A, selectively to HSCs, using an antibody‐liposome targeting vehicle, attenuated carbon tetrachloride‐induced liver fibrosis in mice . In contrast, the current results demonstrate that pharmacologic inhibition of EZH2 degradation is actually protective during biliary fibrosis whereas selective deletion of EZH2 in cholangiocytes exacerbates biliary fibrosis, consistent with our previous finding .…”
Section: Discussionsupporting
confidence: 91%
“…Given that TGF-β-dependent differentiation of fibroblasts to myofibroblasts was associated with increased glucose uptake and glutaminolysis (Bernard et al, 2015(Bernard et al, , 2018Andrianifahanana et al, 2016), it is tempting to speculate that this also applies to the conversion of pericytes to myofibroblasts, although this remains to be demonstrated experimentally. In addition, epigenetic modulation of histone marks may 'lock in' myofibroblast differentiation, as seen in pericytes that exhibited both repressive marks on PPARγ and activating marks on fibrotic genes (Mann et al, 2010;Perugorria et al, 2012;Zeybel et al, 2017).…”
Section: Myofibroblast/smooth Muscle Cell Differentiationmentioning
confidence: 99%
“…Indeed, overexpression of EZH2 induces the expression of fibronectin, α-SMA and collagen 1α1 in primary human HSCs [ 59 ]. In fact, various studies showed that EZH2 inhibitors such as 3-deazaneplanocin A (DZNep) and GSK-503 had antifibrotic properties in in vitro models [ 54 , 59 ] as well as in in vivo models like CCl 4 and BDL-induced liver fibrosis [ 59 , 60 , 61 ]. Mechanistically, a recent study demonstrated that EZH2-mediated suppression of Dkk1 expression, a negative regulator of the Wnt/β-catenin pathway, which is required for HSCs activation [ 61 ].…”
Section: Introductionmentioning
confidence: 99%